A relação entre employer branding e a intenção do colaborador de permanecer na empresa - Rigotti, Vanessa Teresinha (My University, 2023)
The employer brand is the company's efforts to promote within and without itself a clear and concise vision of what makes it unique and appealing as an employer. In the last 20 years, Employer Branding started to be studied and earned popularity as a smart practice for Human Resources managers. The increase in competitiveness between companies to attract and retain talented professionals resulted in an increased interest in understanding the relations between the attractiveness of employer branding and the intention to apply for a job offer and the desire to stay in the company. The intention to stay, which refers to the employee?s conscious willingness to stay in the company, has been studied in Psychology, and later also in Administration, since the 1980s. Regardless of the size of the organization, the difficulties found in recruiting and retaining qualified human capital are the same. In this sense, the goal of this study was to analyze how the dimensions of Employer Branding are related with the intentions, by the employees, to stay in the company. As such, it was performed a research of quantitative nature with the employers of a large-scale company of the metalmechanical sector in the Serra Gaúcha region, in which they answered a survey-type questionnaire addressing the dimensions of the employer branding and the intention to stay in the company. The database was submitted to statistical analysis, including the multiple linear regression, to verify the relations between the studied constructs. The result indicates that the development dimension is the most impactful in the intentions to stay in the company, in which the management implications raise the study of the internal career planning of the company as a fundamental approach to retain talented employees. The economic and interest dimensions also directly influenced the employees? intention to stay, as well as the exchange costs carry the same significance between the groups of employees with more and less time in the company, demonstrating the business capacity to retain professionals in different career moments. [resumo fornecido pelo autor]
A marca do empregador representa os esforços de uma empresa para promover dentro e fora dela uma visão clara e concisa do que a torna diferente e desejável como empregadora. Nos últimos vinte anos, o employer branding passou a ser estudado e ganhou popularidade como uma prática inteligente para os gestores de recursos humanos. O aumento na competitividade entre as empresas para atrair e reter profissionais talentosos resultou em mais interesse em compreender a relação entre as dimensões da atratividade do employer branding e as intenções de se candidatar a uma vaga de emprego e querer permanecer na empresa. A intenção de permanecer, que se refere à vontade consciente do colaborador de permanecer na empresa, vem sendo estudada pela psicologia, e mais tarde também pela administração, desde a década de 1980. Independentemente do tamanho da organização, as dificuldades encontradas para realizar o recrutamento e a retenção de capital humano qualificado são as mesmas. Nesse sentido, o objetivo deste estudo foi analisar como as dimensões do employer branding estão relacionadas à intenção de permanecer na empresa por parte dos funcionários. Para tanto, foi realizada uma pesquisa de natureza quantitativa com os colaboradores de uma empresa de grande porte do setor metalmecânico da Região da Serra Gaúcha, que responderam um questionário do tipo survey abordando as dimensões de employer branding e a intenção de permanecer. O banco de dados foi submetido a análises estatísticas, incluindo a análise de regressão linear múltipla, para que se verificasse as relações entre os construtos estudados. Os resultados indicaram que a dimensão de desenvolvimento é a que mais impacta na intenção de permanecer na empresa, cuja principal implicação gerencial traz o estudo do planejamento de carreira interna da organização como abordagem fundamental para reter colaboradores talentosos. As dimensões econômica e de interesse também influenciam diretamente na intenção de permanecer dos colaboradores, bem como os custos de troca, que são significativos para os grupos com mais tempo de empresa e menos tempo de empresa, demonstrando a capacidade empresarial de reter profissionais em diferentes momentos profissionais. [resumo fornecido pelo autor]
Keywords: Recursos humanos; Administração de pessoal; Marca do empregador; Cultura organizacional; Human resources; Personnel management; Employer branding; Employees - Recruiting; Corporate culture